Motivations and self-regulated learning in MOOCs - Mitsoula, Ioanna; Karatrantou, Anthi; Panagiotopoulou, Penny; Panagiotakopoulos, Christos (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2022)
Massive Open Online Courses (MOOCs) require learners to self-regulate their learning to achieve their goals. Due to MOOCs’ learning autonomy, students must develop strong motivations for learning and self-regulated strategies. The aim of the present study is to investigate learners’ motivations for learning and their self-regulated learning strategies which led some to successfully complete their MOOC, whereas others not. One-hundred-and-twenty (120) learners in xMOOCs, or Coursera-type-MOOCs, took part in the study by completing the MSL-Questionnaire. The results indicated that learners who had completed their MOOC had developed strong motivations of extrinsic orientation, task value, and high self-efficacy. Furthermore, they had used strategies of elaboration and of metacognitive self-regulation. They were able to manage their time and study environment and felt the obligation to keep on studying even when the content of the course did not seem to have any interest on them. Finally, individual differences among the participants, such as gender, year of school graduation, reasons for participating in the MOOC, time for studying, and time dedicated to work per week were found to differentiate both motivations for learning and self-regulated learning strategies.